Moisture Sorption Isotherms and Prediction Models of Carboxymethyl Chitosan Films from Different Sources with Various Plasticizers - Juthamas Tantala (2019)
© 2019 Juthamas Tantala et al. Carboxymethyl chitosan (CMCH) from different chitosan sources (shrimp, crab, and squid) and molecular sizes (polymer and oligomer) were synthesized via carboxymethylation reaction. The CMCH films were prepared by solution casting. All the CMCH films had high water solubility, higher than 85% of the dry matter of the films. The sorption isotherm of the CMCH films was evaluated at several values of relative humidity (0% RH, 23% RH, 34% RH, 43% RH, 65% RH, 77% RH, and 86% RH) at 25 ± 1°C. The equilibrium moisture content values of all the CMCH films were low at lower aw but increased considerably above aw = 0.65. The sigmoidal moisture sorption isotherms of this product can be classified as type II. Understanding of sorption isotherms is an important prerequisite for the prediction of moisture sorption properties of films via moisture sorption empirical models. The experimental data were analyzed and fitted by the nine sorption models. The various constants determined by linear fitting of the sorption equation with r2 values were in the range of 0.7647 to 0.999. The GAB model was found to be the best-fitted model for CMCH films (aw = 0.23-0.86, 25 ± 1°C), and the model presented the optimal root-mean-square percentage error (%RMS) values when compared with other models. In conclusion, it can be stated that the GAB model was found to be better estimated for predicting the CMCH films than other models. Therefore, the constant derived from different sorption models were applied for use in terms of information and for the determination of the stability of CMCH packaging films for specific end uses.